Juridical Review of the Status of Children of Polygamous Marriages Not Approved by the First Wife Under Islamic Law and Indonesian Legislation - Inas Zulfa Sulasno; Eman Suparman; Djanuardi Djanuardi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Polygamy without the consent of the first wife can have legal consequences regarding the marital status of polygamy between husband and second wife and the status of children born to the second wife as a result of sexual intercourse before marriage (pregnant marriage). The purpose of this research was to determine the status of polygamous and the legal status of children born from second wife that were not approved by the first wife. This research uses a normative juridical approach with analytical descriptive research spesifications by conducting literature studies through laws, regulations, and interviews with relevant sources. The analytical method used is juridical qualitative. The result of this research show that the polygamous marital status between the Applicant and the second wife in a state of pregnancy without the consent of the first wife based on Islamic law and laws and regulations in Indonesia is a valid marriage if it meets the conditions, gets along, and there is no prohibition on marriage. The legal status of children born to the second wife in a polygamous marriage in a state of pregnancy that is not approved by the first wife, there is a difference between Islamic Law and the Marriage Law and the KHI. Islamic law uses the minimum gestational age parameter, which is 6 months. If the birth is less than 6 months, then the child is an adulterous child, so it is not confided to the father and uses the guardian of the judge as the guardian of the marriage. Meanwhile, the Marriage Law and IHL states that the status of the child is a legal child without a gestational age limit. The child can be declared to his father and the marriage guardian who can marry the child, namely wali nasab.